2014
DOI: 10.1007/978-3-319-08849-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Holistic Human Pose Estimation with Regression Forests

Abstract: Abstract. In this work, we address the problem of human pose estimation in still images by proposing a holistic model for learning the appearance of the human body from image patches. These patches, which are randomly chosen, are used for extracting features and training a regression forest. During training, a mapping between image features and human poses, defined by joint offsets, is learned; while during prediction, the body joints are estimated with an efficient mode-seeking algorithm. In comparison to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Increasing the variability for a few iterations helps the network to quickly reach a more stable state. Note that we have empirically observed that the number of iterations needed In all datasets (PARSE [48], LSP [19], Football [20] and Volleyball [3]), T ukey s biweight loss function shows, on average, faster convergence and better generalization than L2. Both loss functions are visualised for the same number of epochs.…”
Section: Training Detailsmentioning
confidence: 94%
See 2 more Smart Citations
“…Increasing the variability for a few iterations helps the network to quickly reach a more stable state. Note that we have empirically observed that the number of iterations needed In all datasets (PARSE [48], LSP [19], Football [20] and Volleyball [3]), T ukey s biweight loss function shows, on average, faster convergence and better generalization than L2. Both loss functions are visualised for the same number of epochs.…”
Section: Training Detailsmentioning
confidence: 94%
“…We evaluate Tukey's biweight loss function for the problem of 2D human pose estimation from still images. For that purpose, we have selected four publicly available datasets, namely PARSE [48], LSP [19], Football [20] and Volleyball [3]. All four datasets include sufficient amount of data for training the ConvNets, except for PARSE which has only 100 training images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized trees [165] and random forests [166,167] are fast and robust classification techniques that can handle this type of problem [266]. Random Forest is an ensemble classifier that consists of several randomized decision trees [142,267] and has a nonterminal node containing a decision function to predict the correspondences by regressing from images to terminal nodes, like mesh vertices [9] (Figure 14 shows an example). Enhanced random forests were used by [268], which employed two-layered random forests as joint regressors, with the first layer acting as a discriminative body part classifier and the second one predicting joint locations according to the results of the first layer.…”
Section: Methodologiesmentioning
confidence: 99%
“…By contrast, we choose to apply our model in the operating room scenario which comprises significantly mutual occlusions between the target individuals and thus is much more challenging than the normal ones. In contrary to the concept of part-based models, the holistic models predict directly the body pose by learning a mapping between features and poses [1,6,23,25,29,44,47,59]. One very popular method to accomplish this task are random forests for human pose estimation from depth data [22,42].…”
Section: Related Workmentioning
confidence: 99%